PENGATURAN HUKUM UNDANG - UNDANG NOMOR 9 TAHUN 1961 TENTANG PENGUMPULAN UANG ATAU BARANG TERHADAP PERKEMBANGAN PILANTROPI DI INDONESIA - Furi Rachmawati, (2023)
New advances in various fields have greatly helped human activities, such as the means of collecting donations through online platforms. Online donation-based donation collection has become very popular but there are also concerns of potential abuse. The purpose of this paper is to analyze law enforcement and the legal system on the collection of donations in technological developments based on the donation regulation Law No. 9/1961. The conclusion obtained by the author is that it is known that regulators as supervisors and organizer licensors have not been able to fully apply sanctions to philanthropic actors who commit violations. In addition, Law No. 9/1961 has not been able to respond to changes and developments that occur in society and technology, its implementing laws and regulations have not produced an effective legal system for crowdfunding-based donations.